La conception des maladies de tiédeur dans la médecine chinoise - Dominique Buchillet (Revue d'anthropologie des connaissances)
Since at least two thousand of years, Chinese medicine recognizes the role of abnormal climatic and environmental factors in the appearance of febrile diseases and in the emergence of epidemic outbreaks. Whereas they were mainly attributed in the past to the invasion of the body by pathogenic Wind and Cold, these diseases are since the foundation under the Qing Dynasty (1644-1911) of the School of Warm Diseases also attributed to pathogenic factors of a warm or hot quality, and in the case of epidemic diseases, to “Pestilential Qi” and “Epidemic Warm Toxins” which exist in the environment. This article recounts the evolution of Chinese medical ideas and practices related to exogenous febrile diseases. It will show the evolution of the concept of Warm Diseases during the centuries as well as the importance and role of the epidemic outbreaks in the revision of medical discourses and practices related to these diseases. It comprehends two parts: The first part reviews the fundamental principles of Chinese medicine; the second one recounts the evolution of Chinese medical ideas on the process of development and evolution of exogenous febrile diseases.